A comparison of critical speed and critical power in runners using stryd running power - van Rassel, C. R.; Sales, K. M.; Ajayi, O. O.; Nagai, K.; MacInnis, M. J. (International Journal of Sports Physiology and Performance, 2024)
Purpose: Although running traditionally relies on critical speed (CS) as an indicator of critical intensity, portable inertial measurement units offer a potential solution for estimating running mechanical power to assess critical power (CP) in runners. The purpose of this study was to determine whether CS and CP differ when assessed using the Stryd device, a portable inertial measurement unit, and if 2 running bouts are sufficient to determine CS and CP.